2015
DOI: 10.1016/j.plantsci.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of soil nitrification by plants

Abstract: Nitrification, the biological oxidation of ammonium to nitrate, weakens the soil's ability to retain N and facilitates N-losses from production agriculture through nitrate-leaching and denitrification. This process has a profound influence on what form of mineral-N is absorbed, used by plants, and retained in the soil, or lost to the environment, which in turn affects N-cycling, N-use efficiency (NUE) and ecosystem health and services. As reactive-N is often the most limiting in natural ecosystems, plants have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
127
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 102 publications
3
127
2
3
Order By: Relevance
“…Most of the synthetic inhibitors, such as nitrapyrin, DCD and DMPP, inhibit the Nitrosomonas genus by suppressing the AMO pathway, but have no effect on the HAO pathway. Some BNIs inhibit Nitrosomonas by blockage of both the AMO and HAO pathways (Subbarao et al, 2015). Others, such as methyl 3-(4hydroxyphenyl) propionate (Zakir et al, 2008), inhibit only the AMO pathway, as does 1,9-decanediol.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the synthetic inhibitors, such as nitrapyrin, DCD and DMPP, inhibit the Nitrosomonas genus by suppressing the AMO pathway, but have no effect on the HAO pathway. Some BNIs inhibit Nitrosomonas by blockage of both the AMO and HAO pathways (Subbarao et al, 2015). Others, such as methyl 3-(4hydroxyphenyl) propionate (Zakir et al, 2008), inhibit only the AMO pathway, as does 1,9-decanediol.…”
Section: Researchmentioning
confidence: 99%
“…the very zones in which it is intended to inhibit nitrification (Cahalan et al, 2015). Given these constraints presented by synthetic inhibitors, it is necessary to develop plant-derived nitrification inhibitors, referred to either as natural nitrification inhibitors (NNIs) (Upadhyay et al, 2011) or biological nitrification inhibitors (BNIs) (Subbarao et al, 2015). These are easily available and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that some tree species can inhibit Nitrobacter Soils with low pH and low N availability, typical for most forest Hu et al, 2015), heathland (Bardon et al, 2018) and humid savanna ecosystems (Le Roux et al, 1995), harbour selected plants with diverse mechanisms for improving soil N availability (Chapman et al, 2006). In particular, it has been shown that some plant species in these ecosystems can inhibit nitrifiers (Lata et al, 2004;Subbarao et al, 2009;Srikanthasamy et al, 2018) and that this inhibition is due to the production of specific compounds, often by roots (Subbarao et al, 2006(Subbarao et al, , 2015Coskun et al, 2017). However, most plants previously identified as having a biological nitrification inhibition (BNI) capacity were grass species.…”
Section: Discussionmentioning
confidence: 99%
“…This is termed biological nitrification inhibition (BNI), and there are many documented examples, particularly among tropical grasses (Subbarao et al, 2007). Nitrification is generally inhibited by the exudation of secondary metabolites from roots (Subbarao et al, 2015). However, changes in N transformation rates have also been observed after incorporation of crop tissues into soil; for example, brassica ( Brassica spp.)…”
mentioning
confidence: 99%